Preparation method of acid and alkali resistant positively charged nanofiltration membrane, acid and alkali resistant positively charged nanofiltration membrane and application of acid and alkali resistant positively charged nanofiltration membrane
By grafting quaternary ammonium salt and quaternary phosphorus salt groups on the nanofiltration membrane, the membrane's acid and alkali resistance and positive charge density are improved, and the existing nanofiltration membrane has poor acid resistance and low retention rate in an acidic environment is solved, thereby achieving efficient retention of divalent and high-valent metal ions and taking into account water flux.
Patent Information
- Application Number
- CN202311142229.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-05
AI Technical Summary
The existing nanofiltration membranes have poor acid resistance in acidic environments and have low retention rates for divalent and high-valent metal ions, making it difficult to effectively recover heavy metal ions in electroplating wastewater.
By regulating the specific raw materials and dosage and reaction conditions, a nanofiltration membrane containing chemically inert groups and grafting specific quaternary ammonium salt groups and/or quaternary phosphorus salt groups is prepared to improve the acid and alkali resistance and positive charge density of the membrane, thereby enhancing the retention effect of metal ions.
It achieves a high retention rate of divalent and high-valent metal ions in an acid/alkaline environment, while maintaining good water flux, which is suitable for the treatment of electroplating wastewater.
Smart Images

Figure CN119565385A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanofiltration membranes, and in particular to a method for preparing an acid- and alkali-resistant positively charged nanofiltration membrane, an acid- and alkali-resistant positively charged nanofiltration membrane and applications thereof. Background Art
[0002] Electroplating is a process that uses electrochemical technology to control the surface properties of metals and non-metals to obtain ideal surface corrosion resistance, conductivity, and decorative properties. Electroplating is widely used in my country and produces a large amount of wastewater every year, accounting for about 20% of the total industrial wastewater discharge. Electroplating wastewater contains a large amount of toxic and harmful substances, of which wastewater containing heavy metal ions such as copper, nickel, chromium, and zinc accounts for about 40%, and the pickling activation process commonly used in the electroplating process makes the above wastewater acidic. The comprehensive treatment of acidic electroplating wastewater is a requirement for environmental protection and an effective means of recycling industrial wastewater resources to reduce costs and increase efficiency. At present, the effective recovery of heavy metal ions in electroplating wastewater has become a key issue for the sustainable development of the electroplating industry.
[0003] Conventional chemical precipitation methods have problems such as large amounts of toxic sludge and low recovery rates of heavy metal resources. In comparison, membrane separation technology has the characteristics of high separation efficiency, no secondary pollution, low energy consumption, and easy operation. It has been widely used to recover metal ions such as copper, nickel, chromium, and zinc from electroplating wastewater. Among them, nanofiltration separation has good application prospects in the above process. It is generally believed that nanofiltration separation performance is the result of the combined effects of size screening effect and Donnan effect. In addition to the density of the membrane itself, the nanofiltration separation process has significant charge selectivity. Polyamide film composite nanofiltration membrane is the most widely used commercial nanofiltration membrane. The acyl chloride groups on the membrane surface are hydrolyzed to form a large number of carboxyl groups, making the membrane surface negatively charged. Due to the influence of the Donnan effect, the membrane has a low removal rate for high-valent cations, resulting in a low recovery rate for metal ions such as copper, nickel, chromium, and zinc.
[0004] In addition to the charged properties of the membrane, the treatment of acidic electroplating wastewater also has higher requirements for the membrane's acid resistance. Under acidic conditions, the C=O bond in the structure of conventional polyamide nanofiltration membranes is easily affected by H + The nucleophilic electrons attack the amide bonds, causing hydrolysis of the amide bonds, which destroys the structure of the membrane separation layer and reduces the interception performance. In order to ensure the structural stability of the nanofiltration membrane, the pH of the influent needs to be adjusted, which not only increases the dosage of the reagent, but also makes the treatment process more complicated.
[0005] Therefore, there is an urgent need to develop a positively charged nanofiltration membrane with a simple preparation method and excellent acid resistance to enhance the Donnan effect in the nanofiltration separation process and achieve effective recovery of high-valent heavy metal cations. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems that the nanofiltration membrane prepared by the prior art has poor acid and alkali resistance and low interception rate for divalent and high-valent metal ions, and to provide a preparation method of an acid- and alkali-resistant positively charged nanofiltration membrane, an acid- and alkali-resistant positively charged nanofiltration membrane and applications thereof. The present invention regulates specific raw materials, dosages and reaction conditions so that the prepared nanofiltration membrane contains chemically inert groups and is grafted with specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups. The nanofiltration membrane has an excellent interception effect for divalent and high-valent metal ions while maintaining a high water flux, and can be used in acidic / alkaline environments and can be used for the treatment of acidic electroplating wastewater.
[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an acid-base resistant positively charged nanofiltration membrane, wherein the method comprises the following steps:
[0008] S1, sequentially preparing a porous support layer and an acid-base resistant separation layer on the bottom layer to obtain a composite membrane;
[0009] S2. Contacting the composite membrane with an aqueous solution containing a catalyst, a halogenated quaternary ammonium salt and / or a halogenated quaternary phosphonium salt, and drying the mixture to obtain the acid- and alkali-resistant positively charged nanofiltration membrane.
[0010] The second aspect of the present invention provides an acid-base resistant positively charged nanofiltration membrane prepared by the aforementioned preparation method.
[0011] The third aspect of the present invention provides an application of the aforementioned acid-base resistant positively charged nanofiltration membrane in the field of water treatment.
[0012] Through the above technical solution, the technical solution provided by the present invention achieves the following beneficial effects:
[0013] The acid- and alkali-resistant positively charged nanofiltration membrane prepared by the preparation method provided by the present invention contains good chemically inert groups and has a high hydrogen bond density, so that the nanofiltration membrane has good acid and alkali resistance; and then specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups are grafted, so that the positive charge density on the surface of the nanofiltration membrane is significantly improved, and the repulsive effect between the positive charges is utilized to improve the retention effect of the nanofiltration membrane on divalent and high-valent heavy metal ions, while maintaining good water flux. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the XPS phosphorus element fine spectrum of the surface of the acid- and alkali-resistant composite nanofiltration membrane prepared in Example 1. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] The first aspect of the present invention provides a method for preparing an acid-base resistant positively charged nanofiltration membrane, wherein the method comprises the following steps:
[0017] S1, sequentially preparing a porous support layer and an acid-base resistant separation layer on the bottom layer to obtain a composite membrane;
[0018] S2. Contacting the composite membrane with an aqueous solution containing a catalyst, a halogenated quaternary ammonium salt and / or a halogenated quaternary phosphonium salt, and drying the mixture to obtain the acid- and alkali-resistant positively charged nanofiltration membrane.
[0019] In the present invention, the acid-base resistant positively charged nanofiltration membrane contains chemically inert groups that can be used in acid / alkaline environments, and is grafted with specific quaternary ammonium salt groups and / or quaternary phosphonium salt groups, so that the nanofiltration membrane has a high retention rate for divalent and high-valent metal ions while maintaining a high water flux.
[0020] In the present invention, the ratio of the amount of the aqueous solution containing the catalyst, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt to the membrane area of the composite membrane is 0.1-1 g / cm 2 , preferably 0.3-0.5g / cm 2 .
[0021] In the present invention, the bottom layer and the porous support layer are not specifically limited and can be made of various existing materials that have certain strength and can be used for nanofiltration and reverse osmosis membranes.
[0022] In the present invention, the bottom layer is a non-woven fabric, preferably polyester and / or polyethylene.
[0023] In the present invention, the porous support layer material is at least one selected from polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.
[0024] In the present invention, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer, preferably at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.
[0025] Furthermore, the acid-base resistant separation layer is generated by interfacial polymerization of polyamines and polypolar monomers.
[0026] In the present invention, the process of interfacial polymerization includes first contacting the surface of the porous support layer with an aqueous phase containing polyamines, and then second contacting the surface of the porous support layer with an organic phase containing polyamine polar monomers, followed by heat treatment.
[0027] The reaction conditions for the first contact, the second contact and the heat treatment are conventional conditions in the art. Preferably, the time of the first contact is 5-100s, preferably 10-60s; the temperature of the first contact is 15-50°C, preferably 20-40°C; the time of the second contact is 10-200s, preferably 20-120s; the temperature of the second contact is 15-40°C, preferably 20-30°C; the conditions for the heat treatment include: the heat treatment time is 0.5-10min, preferably 1-5min; the heat treatment temperature is 40-150°C, preferably 50-120°C.
[0028] According to the present invention, the polyvalent polar monomer is selected from at least one of polyvalent isocyanates, triazine compounds containing at least two C-Cl bonds, and polyvalent sulfonyl chlorides.
[0029] The polyamine reacts with at least one of polyisocyanate, triazine compound containing at least two C-Cl bonds and polysulfonyl chloride to introduce groups with strong conjugation effect and good chemical inertness into the nanofiltration membrane. The polymer contained in the generated acid-base resistant separation layer has good structural stability in both acidic and alkaline environments, so that the acid-base resistance of the nanofiltration membrane is greatly improved and is particularly suitable for acidic environments.
[0030] According to the present invention, the polyamine is at least one of polyethyleneimine, polyethyleneamine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine; preferably polyethyleneimine and / or polyethylenepolyamine.
[0031] According to the present invention, the polyisocyanate is selected from at least one of meta-phenylenediisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl meta-phenylene diisocyanate; preferably 1,4-phenylene diisocyanate and / or 1,3-phenylene diisocyanate.
[0032] According to the present invention, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine; preferably cyanuric chloride.
[0033] According to the present invention, the polysulfonyl chloride is selected from at least one of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 1,3-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, 1,3,5-benzene trisulfonyl chloride and 1,3,6-naphthalene trisulfonyl chloride; preferably 1,3-benzenedisulfonyl chloride.
[0034] According to the present invention, the weight ratio of the polyamine in the aqueous phase to the polyvalent polar monomer in the organic phase is 2-200:1, preferably 5-80:1.
[0035] According to the present invention, the concentration of the polyamine in the aqueous phase is 0.1 wt%-10 wt%, preferably 0.5 wt%-2.5 wt%.
[0036] According to the present invention, the concentration of the multi-polar monomer in the organic phase is 0.01 wt%-2 wt%, preferably 0.05 wt%-1 wt%.
[0037] In the present invention, the ratio of the amount of the aqueous phase containing the polyamine to the membrane area of the porous support layer is 0.05-0.5 g / cm 2 , preferably 0.1-0.3 g / cm 2 .
[0038] In the present invention, the ratio of the amount of the organic phase containing the multi-polar monomer to the membrane area of the porous support layer is 0.03-0.3 g / cm 2 , preferably 0.05-0.2g / cm 2 .
[0039] According to the present invention, wherein the halogenated quaternary ammonium salt has a structure shown in Formula I; the halogenated quaternary phosphonium salt has a structure shown in Formula II;
[0040]
[0041] Wherein, R1' is a substituted or unsubstituted alkylene group of C1-C9; R2', R3', and R4' are each independently selected from a C1-C3 alkyl group or a phenyl group; R5' is a C1-C6 alkylene group, a phenyl group, or a C7-C10 aralkyl group; R6', R7', and R8' are each independently selected from a phenyl group or a C7-C10 aralkyl group;
[0042] X and X1 are each independently halogen.
[0043] Further, R1' is a C1-C6 substituted or unsubstituted alkylene group; R2', R3', and R4' are each independently CH3; R5' is a C1-C3 alkylene group, a phenyl group, or a C8-C10 aralkyl group; R6', R7', and R8' are each independently phenyl groups.
[0044] Furthermore, R1' is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group.
[0045] Furthermore, X is Cl, Br or I.
[0046] Furthermore, X1 is F, Cl, Br or I.
[0047] In one embodiment of the present invention, in Formula I, R1' is ethylene, R2', R3', R4' are methyl, ethyl or phenyl; X is Cl, Br or I.
[0048] In one embodiment of the present invention, in formula II, R5' is propylene, ethylene, methylene or R6', R7', R8' are phenyl groups; X is Cl, Br or I.
[0049] According to the present invention, in step S2, the contacting method is a common contacting method in the art, preferably immersion.
[0050] According to the present invention, the contact time is 10s-10min; the contact temperature is 20-80°C.
[0051] In the present invention, when the contact conditions are controlled to meet the above range, it can ensure that the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt react fully on the membrane surface, thereby increasing the positive charge density on the membrane surface, so that the nanofiltration membrane has good retention capacity for divalent and high-valent metal ions while maintaining a high water flux; and the process is compatible with the existing industrial continuous production process and is suitable for scaled-up preparation.
[0052] Furthermore, the contact time is 20s-1min; the contact temperature is 30-50°C.
[0053] According to the present invention, the drying time is 0.5-10 min; the drying temperature is 40-80°C.
[0054] In the present invention, when the drying conditions are controlled to meet the above range, the grafting reaction of halogenated quaternary ammonium salts and / or halogenated quaternary phosphonium salts on the surface of the acid-base resistant separation layer can be promoted to proceed further, and the positive charge density on the membrane surface is further improved, thereby further enhancing the nanofiltration membrane's ability to retain divalent and high-valent metal ions and ensuring a higher water flux; at the same time, the process is compatible with the existing industrial continuous production process and can be scaled up for mass production.
[0055] Furthermore, the drying time is 3-5 minutes; the drying temperature is 50-70°C.
[0056] According to the present invention, in step S2, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, disodium hydrogen phosphate and dipotassium hydrogen phosphate; preferably potassium hydroxide.
[0057] According to the present invention, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide; preferably 2-chloroethyltrimethylammonium chloride and / or 3-bromopropyltrimethylammonium bromide.
[0058] According to the present invention, the halogenated quaternary phosphonium salt is selected from 3-bromopropyl triphenyl phosphonium bromide, 2-bromoethyl triphenyl phosphonium bromide, 1-bromoethyl triphenyl phosphonium bromide, bromomethyl triphenyl phosphonium bromide, 3-chloropropyl triphenyl phosphonium chloride, 2-chloroethyl triphenyl phosphonium chloride, 1-chloroethyl triphenyl phosphonium chloride, chloromethyl triphenyl phosphonium chloride, 3-iodopropyl triphenyl phosphonium iodide, 2-iodoethyl triphenyl phosphonium iodide, 1-iodoethyl triphenyl phosphonium iodide, iodomethyl triphenyl phosphonium bromide, 4-bromomethyl At least one of benzyltriphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide, 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide; preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide.
[0059] According to the present invention, the concentration of the catalyst in the aqueous solution is 0.01 wt%-5 wt%.
[0060] In the present invention, when the concentration of the catalyst in the aqueous solution is controlled to meet the above range, the reaction of the grafted quaternary ammonium halides and / or quaternary phosphonium halides on the membrane surface can be more fully carried out without causing waste of the catalyst, thereby improving the economic efficiency of the process.
[0061] Furthermore, the concentration of the catalyst in the aqueous solution is 0.1wt%-1wt%.
[0062] According to the present invention, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the aqueous solution is 1 wt%-20 wt%.
[0063] In the present invention, when the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the aqueous solution is controlled to meet the above range, the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt can be fully grafted on the membrane surface, thereby increasing the surface charge density of the acid-base resistant positively charged nanofiltration membrane, thereby increasing the retention rate of the nanofiltration membrane for divalent and high-valent metal ions, while causing no waste and improving the economy of the process.
[0064] Furthermore, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the aqueous solution is 5wt%-10wt%.
[0065] The second aspect of the present invention provides an acid-base resistant positively charged nanofiltration membrane prepared by the aforementioned preparation method.
[0066] According to the present invention, the acid-base resistant positively charged nanofiltration membrane comprises a bottom layer, a porous support layer and an acid-base resistant separation layer in sequence;
[0067] Wherein, the acid-base resistant separation layer is grafted with a quaternary ammonium salt group represented by formula I and / or a quaternary phosphonium salt group represented by formula II via N atoms;
[0068]
[0069] Wherein, R1 is a substituted or unsubstituted alkylene group of C1-C9; R2, R3, and R4 are each independently selected from a C1-C3 alkyl group or a phenyl group; R5 is a C1-C6 alkylene group, a phenyl group, or a C7-C10 aralkyl group; R6, R7, and R8 are each independently selected from a phenyl group or a C7-C10 aralkyl group;
[0070] X is halogen.
[0071] Furthermore, R1 is a C1-C6 substituted or unsubstituted alkylene group, R2, R3, and R4 are each independently CH3; R5 is a C1-C3 alkylene group, a phenyl group, or a C8-C10 aralkyl group; and R6, R7, and R8 are each independently phenyl groups.
[0072] Furthermore, R1 is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group.
[0073] Furthermore, X is Cl, Br or I.
[0074] According to the present invention, the content of nitrogen atoms in the quaternary ammonium salt groups in the acid-base resistant positively charged nanofiltration membrane is 0.5-6 at.%.
[0075] In the present invention, when the content of nitrogen atoms in the quaternary ammonium salt groups in the acid- and alkali-resistant positively charged nanofiltration membrane meets the above range, the acid- and alkali-resistant positively charged nanofiltration membrane has a high surface electrode potential and a small average pore size, so that the acid- and alkali-resistant positively charged nanofiltration membrane has good retention performance for divalent and high-valent heavy metal cations; at the same time, the acid- and alkali-resistant separation layer will not excessively affect the water flux of the membrane through the quaternary ammonium salt groups shown in the nitrogen atom grafting formula I.
[0076] Furthermore, the content of nitrogen atoms in the acid-base resistant positively charged nanofiltration membrane is 2-5 at.%.
[0077] According to the present invention, the content of phosphorus atoms in the acid-base resistant positively charged nanofiltration membrane is 0.4-3 at.%.
[0078] In the present invention, when the content of phosphorus atoms in the acid- and alkali-resistant positively charged nanofiltration membrane meets the above-mentioned range, the acid- and alkali-resistant positively charged nanofiltration membrane has a high surface electrode potential and a small average pore size, so that the acid- and alkali-resistant positively charged nanofiltration membrane has good retention performance for divalent and high-valent heavy metal cations; at the same time, the acid- and alkali-resistant separation layer will not excessively affect the water flux of the membrane through the quaternary phosphonium salt group shown in nitrogen atom grafting formula II, and the membrane can have good separation efficiency.
[0079] Furthermore, the content of phosphorus atoms in the acid-base resistant positively charged nanofiltration membrane is 0.5-2 at.%.
[0080] According to the present invention, the surface Zeta potential of the acid-base resistant positively charged nanofiltration membrane is 0-30 mV.
[0081] In the present invention, the surface Zeta potential of the acid- and alkali-resistant positively charged nanofiltration membrane refers to the surface Zeta potential at pH=7.
[0082] In the present invention, when the surface Zeta potential of the acid- and alkali-resistant positively charged nanofiltration membrane meets the above range, it indicates that the composite nanofiltration membrane has a high surface electrode potential. When it is used for separating high-valent heavy metal ions in an acid- and alkali environment, it can better repel high-valent heavy metal ions, making it difficult for high-valent heavy metal ions in the liquid to pass through the nanofiltration membrane, thereby achieving effective recovery of high-valent heavy metal cations.
[0083] Furthermore, the surface Zeta potential of the acid- and alkali-resistant positively charged nanofiltration membrane is 5-20 mV.
[0084] According to the present invention, the average pore size of the acid-base resistant positively charged nanofiltration membrane is 0.1-0.5 nm.
[0085] In the present invention, when the average pore size of the acid- and alkali-resistant positively charged nanofiltration membrane meets the above range, it indicates that the acid- and alkali-resistant positively charged nanofiltration membrane has a high density. When it is used for the separation of high-valent heavy metal ions in an acid- and alkali environment, it can better repel high-valent heavy metal ions, making it difficult for high-valent ions in the liquid to pass through the nanofiltration membrane, thereby obtaining a higher separation efficiency of high-valent heavy metal ions.
[0086] Furthermore, the average pore size of the acid-base resistant positively charged nanofiltration membrane is 0.15-0.3 nm.
[0087] According to the present invention, the contact angle of the acid-base resistant positively charged nanofiltration membrane is 30-80°.
[0088] In the present invention, the acid-base resistant positively charged nanofiltration membrane has a contact angle within the range of the present invention, which indicates that the acid-base resistant positively charged nanofiltration membrane has excellent hydrophilicity and can make the acid-base resistant positively charged nanofiltration membrane have high water flux.
[0089] Furthermore, the contact angle of the acid-base resistant positively charged nanofiltration membrane is 30-60°.
[0090] In the present invention, the bottom layer and the porous support layer are not specifically limited and can be made of various existing materials that have certain strength and can be used for nanofiltration and reverse osmosis membranes.
[0091] In the present invention, the bottom layer is a non-woven fabric, preferably polyester and / or polyethylene.
[0092] In the present invention, the porous support layer material is at least one selected from polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.
[0093] In the present invention, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer, preferably at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.
[0094] According to the present invention, the present invention does not particularly limit the thickness of the bottom layer, the porous support layer, and the acid-base resistant separation layer, which is a conventional choice in the art. However, in order to enable the three layers to play a better synergistic role, the obtained acid-base resistant positively charged nanofiltration membrane can better have both excellent high-valent heavy metal ion separation coefficient and higher water flux, preferably, the thickness of the bottom layer is 30-150μm, preferably 50-120μm; the thickness of the porous support layer is 10-100μm, preferably 30-60μm; the thickness of the acid-base resistant separation layer is 10-500nm, preferably 50-300nm.
[0095] The third aspect of the present invention provides an application of the aforementioned acid-base resistant positively charged nanofiltration membrane in the field of water treatment.
[0096] In the present invention, the NiCl2 retention rate of the acid-base resistant positively charged nanofiltration membrane is ≥85%, preferably ≥89%; the CuCl2 retention rate is ≥88%, preferably ≥88.5%; and the water flux is ≥22LMH, preferably ≥24LMH.
[0097] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0098] The present invention will be described in detail below through examples.
[0099] (1) The water flux of the acid-base resistant positively charged nanofiltration membrane is tested by the following method: the nanofiltration membrane is placed in a membrane pool, pre-pressed at 1.5 MPa for 1 h, and the water permeation of the acid-base resistant positively charged nanofiltration membrane is measured under the conditions of a pressure of 2 MPa and a temperature of 25°C within a certain period of time. The water flux is calculated by the following formula:
[0100] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective filtration membrane area of the acid- and alkali-resistant positively charged nanofiltration membrane (m 2 ), t is time (h).
[0101] (2) The retention rate of the acid-base resistant positively charged nanofiltration membrane was tested by the following method: the acid-base resistant positively charged nanofiltration membrane was placed in a membrane pool, pre-pressed at 1.5 MPa for 1 h, and the concentration changes of the salt in the raw aqueous solution and the permeate with an initial concentration of 2000 ppm within 1 h were tested under the conditions of pressure of 2 MPa and temperature of 25°C. The retention rate was calculated by the following formula:
[0102] R=(C f -C p ) / C f × 100%, where R is the interception rate, C f is the concentration of NiCl2 or CuCl2 in the original aqueous solution (measured by conductivity meter), C pis the concentration of NiCl2 or CuCl2 in the permeate.
[0103] (4) Acid resistance test method for positively charged nanofiltration membrane: The nanofiltration membrane was immersed in a 5 wt% HCl solution for 7 days, taken out and thoroughly cleaned, and then the water flux and high-valent heavy metal ion retention rate of the nanofiltration membrane were tested.
[0104] (5) Determination of contact angle on the surface of acid-base resistant positively charged nanofiltration membrane
[0105] The surface contact angle of the nanofiltration membrane sample was tested by the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample was dried in a 60°C vacuum oven for 30 minutes to remove surface and internal moisture, and then the dried membrane was attached to a flat glass slide with double-sided tape. The volume of each water drop was 2 μL during the test. The water drop was dropped on the membrane surface for 3 seconds and then tested immediately. The average value was taken after multiple measurements to determine the final contact angle.
[0106] (6) Determination of nitrogen atoms in quaternary ammonium salt groups on the surface of acid- and alkali-resistant positively charged nanofiltration membranes and phosphorus atoms in nanofiltration membranes:
[0107] Before measurement, the sample was dried in an oven to constant weight, and the elemental composition of the nanofiltration membrane sample surface was determined using a Sigma Probe X-ray photoelectron spectrometer produced by Thermo VG, UK. For samples containing quaternary ammonium salt groups, the molar content of nitrogen atoms in the quaternary ammonium salt group is equal to the corresponding molar content of halogens, and the content of nitrogen atoms in the quaternary ammonium salt group is determined by the measured halogen content; the content of phosphorus atoms in quaternary phosphonium salts can be directly measured by XPS spectra.
[0108] (7) Acid and alkali resistant positively charged nanofiltration membrane pore size test: PEG solute transfer method is used for measurement. The detailed steps are as follows:
[0109] (i) Testing the retention rate of PEG with different molecular sizes by acid-base resistant positively charged nanofiltration membrane;
[0110] (ii) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the nanofiltration membrane.
[0111] (8) Zeta potential test of the surface of acid- and alkali-resistant positively charged nanofiltration membrane: The test was carried out using a Surpass electrokinetic analyzer (Anton Paar). The circulating fluid was a dilute aqueous solution of KCl and the pH of the test fluid was 7.
[0112] In addition, in the following examples and comparative examples:
[0113] Branched polyethyleneimine (weight average molecular weight of 25000 g / mol), polyethylene polyamine, 1,4-phenylene diisocyanate, cyanuric chloride, 1,3-phenylenedisulfonyl chloride, 3-bromopropyltriphenylphosphonium bromide, chloromethyltriphenylphosphonium chloride, 2-chloroethyltrimethylammonium chloride, 3-bromopropyltrimethylammonium bromide, etc. were purchased from J&K Technology Co., Ltd.
[0114] Other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0115] The supporting layer is prepared by a phase inversion method, and the specific steps are as follows:
[0116] A certain amount of polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min; then, the polysulfone solution was coated on a polyester non-woven fabric (75 μm thick) using a scraper to obtain an initial membrane, which was then immersed in water at a temperature of 25°C for 60 min to allow the polysulfone layer on the surface of the polyester non-woven fabric to undergo phase transformation into a porous membrane, and finally washed with water three times to obtain a support layer with a total thickness of 115 μm, which included a bottom layer and a porous support layer.
[0117] Example 1
[0118] 400cm 2 The upper surface of the polysulfone support layer is contacted with 50 g of an aqueous solution containing 0.5 wt% polyethyleneimine, and the solution is discharged after the contact is maintained at 25° C. for 60 seconds; then, the upper surface of the support layer is contacted with 30 g of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate, and the solution is discharged after the contact is maintained at 25° C. for 60 seconds; then, the membrane is placed in an oven and heated at 70° C. for 3 minutes to obtain a composite membrane A1;
[0119] At 30°C, the composite membrane A1 was immersed in an aqueous solution containing 150 g of 10 wt% 3-bromopropyltriphenylphosphonium bromide and 0.5 wt% potassium hydroxide for 1 minute, then taken out and dried at 70°C for 5 minutes to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N1;
[0120] The XPS phosphorus atomic spectrum of the acid-base resistant positively charged nanofiltration membrane N1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the signal of phosphorus element on the membrane surface is obvious (the prominent single peak in the figure), indicating that the acid-base resistant separation layer successfully grafts the quaternary phosphine salt group shown in formula I through the N atom, thereby enhancing the positive charge of the acid-base resistant positively charged nanofiltration membrane surface and the retention effect of divalent and high-valent heavy metal ions.
[0121] Example 2
[0122] 400cm2 The upper surface of the polysulfone support layer is contacted with 50g of an aqueous solution containing 0.5wt% polyethylene polyamine, and the solution is discharged after contacting at 25°C for 60s; then, the upper surface of the support layer is contacted with 30g of an Isopar E solution containing 0.1wt% 1,4-phenylene diisocyanate, and the solution is discharged after contacting at 25°C for 60s; then, the membrane is placed in an oven and heated at 70°C for 3min to obtain a composite membrane A2;
[0123] At 30°C, the composite membrane A2 was immersed in an aqueous solution containing 150g of 5wt% 3-bromopropyltriphenylphosphonium bromide and 0.5wt% potassium hydroxide for 1 minute, and then taken out and dried at 70°C for 5 minutes to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N2.
[0124] Example 3
[0125] The method of Example 1 is followed, except that "chloromethyl triphenyl phosphonium chloride" is used instead of "3-bromopropyl triphenyl phosphonium bromide" to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N3.
[0126] Example 4
[0127] The method of Example 1 was followed, except that "2-chloroethyltrimethylammonium chloride" was used instead of "3-bromopropyltriphenylphosphonium bromide" to obtain a quaternary ammonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N4.
[0128] Example 5
[0129] The method of Example 1 was followed, except that "3-bromopropyltrimethylammonium bromide" was used instead of "3-bromopropyltriphenylphosphonium bromide" to obtain a quaternary ammonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N5.
[0130] Example 6
[0131] The method of Example 1 is followed, except that "2 wt % aqueous solution of polyethyleneimine" is used instead of "0.5 wt % aqueous solution of polyethyleneimine", and "0.05 wt % Isopar E solution of cyanuric chloride" is used instead of "0.1 wt % Isopar E solution of 1,4-phenylene diisocyanate", to obtain a quaternary phosphonium salt-modified acid and alkali resistant positively charged nanofiltration membrane N6.
[0132] Example 7
[0133] The method of Example 1 is followed, except that "2 wt % aqueous solution of polyethyleneimine" is used instead of "0.5 wt % aqueous solution of polyethyleneimine", and "0.2 wt % Isopar E solution of 1,3-benzenedisulfonyl chloride" is used instead of "0.1 wt % Isopar E solution of 1,4-phenylenediisocyanate", to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N7.
[0134] Example 8
[0135] The method of Example 1 is followed, except that "20 wt % of 3-bromopropyltriphenylphosphonium bromide" is used instead of "10 wt % of 3-bromopropyltriphenylphosphonium bromide" to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N8.
[0136] Example 9
[0137] The method of Example 1 is followed, except that "0.1 wt % of 3-bromopropyltriphenylphosphonium bromide" is used instead of "10 wt % of 3-bromopropyltriphenylphosphonium bromide" to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N9.
[0138] Example 10
[0139] The method of Example 1 was followed, except that "0.01 wt % potassium hydroxide" was used instead of "0.5 wt % potassium hydroxide" to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N10.
[0140] Embodiment 11
[0141] The method of Example 1 was followed, except that "0.005 wt % potassium hydroxide" was used instead of "0.5 wt % potassium hydroxide" to obtain a quaternary phosphonium salt-modified acid- and alkali-resistant positively charged nanofiltration membrane N11.
[0142] Example 12
[0143] The method of Example 1 was followed, except that the contact time was 10 seconds, to obtain the acid- and alkali-resistant positively charged nanofiltration membrane N12 modified with quaternary phosphate.
[0144] Embodiment 13
[0145] The method of Example 1 was followed, except that the contact temperature was 20° C., to obtain a quaternary phosphate-modified acid- and alkali-resistant positively charged nanofiltration membrane N13.
[0146] Comparative Example 1
[0147] The upper surface of the polysulfone support layer was contacted with 50 g of an aqueous solution containing 0.5 wt% polyethyleneimine at 25°C for 60 seconds, and then the liquid was drained; then, the upper surface of the support layer was contacted with 30 g of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate at 25°C for 60 seconds, and then the liquid was drained; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane D1.
[0148] Comparative Example 2
[0149] The process was carried out in the same manner as in Example 1, except that no catalyst was added, to obtain a composite membrane D2.
[0150] The acid-base resistant positively charged nanofiltration membrane prepared in the example and the composite membrane prepared in the comparative example were tested for thickness, surface Zeta potential, contact angle and average pore size. The results are shown in Table 1 and Table 2.
[0151] Table 1
[0152] Bottom layer thickness (μm) Porous support layer thickness (μm) Acid and alkali resistant separation layer thickness (nm) N1 75 40 139 N2 75 40 134 N3 75 40 140 N4 75 40 138 N5 75 40 136 N6 75 40 157 N7 75 40 179 N8 75 40 154 N9 75 40 135 N10 75 40 138 N11 75 40 134 N12 75 40 135 N13 75 40 137 D1 75 40 132 D2 75 40 133
[0153] Note: The thickness of the acid-base resistant separation layer here refers to the acid-base resistant separation layer modified with quaternary ammonium salt and / or halogenated quaternary phosphonium salt.
[0154] Table 2
[0155]
[0156]
[0157] Note: a - The content of nitrogen atoms in the quaternary ammonium salt groups in the acid- and alkali-resistant positively charged nanofiltration membrane;
[0158] b -The content of phosphorus atoms in acid- and alkali-resistant positively charged nanofiltration membranes;
[0159] “-” means it cannot be measured.
[0160] The acid-base resistant positively charged nanofiltration membrane prepared in the embodiment and the composite membrane prepared in the comparative example were tested for the retention rate and water flux of NiCl2 and CuCl2, respectively; after the acid-resistant positively charged nanofiltration membrane prepared in the embodiment and the composite membrane prepared in the comparative example were treated with acid, the retention rate and water flux of NiCl2 and CuCl2 were tested, respectively, and the results are shown in Table 3.
[0161] Table 3
[0162]
[0163]
[0164] It can be seen from Examples 1-7 that the acid- and alkali-resistant positively charged nanofiltration membrane prepared by the preparation method of the present invention has good acid and alkali resistance, and takes into account both the interception effect of divalent and high-valent heavy metal ions and a higher water flux.
[0165] It can be seen from Example 1, Example 8, and Example 9 that the concentration of the halogenated quaternary phosphonium salt is fully grafted on the membrane surface, which increases the surface charge density of the acid- and alkali-resistant positively charged nanofiltration membrane, thereby increasing the retention rate of the nanofiltration membrane for divalent and high-valent metal ions, while also having a higher water flux; when the concentration of the halogenated quaternary phosphonium salt is too low, the retention rate decreases; when the concentration of the halogenated quaternary phosphonium salt is too high, it will cause a decrease in water flux and waste of raw materials.
[0166] It can be seen from Example 1, Example 10, and Example 11 that the appropriate catalyst concentration of the present invention can make the reaction of the grafted quaternary ammonium halides and / or quaternary phosphonium halides on the membrane surface proceed more fully, thereby improving the retention rate of the nanofiltration membrane for divalent and high-valent metal ions while having a higher water flux.
[0167] In Comparative Example 1, no modification with halogenated quaternary ammonium salt and / or halogenated quaternary phosphonium salt was performed, and the interception rate of the obtained nanofiltration membrane for divalent and high-valent metal ions decreased, and effective interception of divalent and high-valent metal ions could not be achieved.
[0168] No catalyst was added in Comparative Example 2. From the data in Table 1, it can be seen that the surface Zeta potential of the composite membrane is lower and the phosphorus atom content is lower, which can prove that the acid-base resistant separation layer is not sufficiently grafted. From the data in Table 2, it can also be seen that the retention rate of the composite membrane for NiCl2 and CuCl2 is reduced.
[0169] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing an acid- and alkali-resistant positively charged nanofiltration membrane, characterized in that: The method comprises the following steps: S1, sequentially preparing a porous support layer and an acid-base resistant separation layer on the bottom layer to obtain a composite membrane; S2. Contacting the composite membrane with an aqueous solution containing a catalyst, a halogenated quaternary ammonium salt and / or a halogenated quaternary phosphonium salt, and drying the mixture to obtain the acid- and alkali-resistant positively charged nanofiltration membrane.
2. The preparation method according to claim 1, wherein The halogenated quaternary ammonium salt has a structure shown in Formula I; the halogenated quaternary phosphonium salt has a structure shown in Formula II; Wherein, R1' is a substituted or unsubstituted alkylene group of C1-C9; R2', R3', and R4' are each independently selected from a C1-C3 alkyl group or a phenyl group; R5' is a C1-C6 alkylene group, a phenyl group, or a C7-C10 aralkyl group; R6', R7', and R8' are each independently selected from a phenyl group or a C7-C10 aralkyl group; X and X1 are each independently halogen; Preferably, R1' is a C1-C6 substituted or unsubstituted alkylene group; R2', R3', and R4' are each independently CH3; R5' is a C1-C3 alkylene group, a phenyl group, or a C8-C10 aralkyl group; R6', R7', and R8' are each independently phenyl groups; Preferably, R1' is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group, preferably a hydroxyl group; Preferably, X is Cl, Br or I; Preferably, X1 is F, Cl, Br or I.
3. The preparation method according to claim 1 or 2, wherein In step S2, the contacting method is immersion; Preferably, the contact time is 10s-10min, preferably 20s-1min; the contact temperature is 20-80°C, preferably 30-50°C; Preferably, the drying time is 0.5-10 min, preferably 3-5 min; the drying temperature is 40-80°C, preferably 50-70°C.
4. The preparation method according to any one of claims 1 to 3, wherein In step S2, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, disodium hydrogen phosphate and dipotassium hydrogen phosphate; preferably potassium hydroxide; Preferably, the halogenated quaternary ammonium salt is selected from at least one of 2-chloroethyltrimethylammonium chloride, 2-chloroethyltriethylammonium chloride, 2-chloroethyltriphenylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-chloropropyltrimethylammonium chloride, 4-chlorobutyltrimethylammonium chloride, 5-chloropentyltrimethylammonium chloride, 6-chlorohexyltrimethylammonium chloride, 2-bromoethyltrimethylammonium bromide, 3-bromopropyltrimethylammonium bromide, 4-bromobutyltrimethylammonium bromide, 5-bromopentyltrimethylammonium bromide, 6-bromohexyltrimethylammonium bromide, iodomethyltrimethylammonium iodide, 2-iodoethyltrimethylammonium iodide, 3-iodopropyltrimethylammonium iodide, 4-iodobutyltrimethylammonium iodide, 5-iodopentyltrimethylammonium iodide and 6-iodohexyltrimethylammonium iodide; preferably 2-chloroethyltrimethylammonium chloride and / or 3-bromopropyltrimethylammonium bromide; Preferably, the halogenated quaternary phosphonium salt is selected from 3-bromopropyltriphenylphosphonium bromide, 2-bromoethyltriphenylphosphonium bromide, 1-bromoethyltriphenylphosphonium bromide, bromomethyltriphenylphosphonium bromide, 3-chloropropyltriphenylphosphonium chloride, 2-chloroethyltriphenylphosphonium chloride, 1-chloroethyltriphenylphosphonium chloride, chloromethyltriphenylphosphonium chloride, 3-iodopropyltriphenylphosphonium iodide, 2-iodoethyltriphenylphosphonium iodide, 1-iodoethyltriphenylphosphonium iodide, iodomethyltriphenylphosphonium bromide, 4-bromomethylbenzylphosphonium At least one of 2-bromomethylbenzyltriphenylphosphonium bromide, 2-bromomethylbenzyltriphenylphosphonium bromide, 3-bromomethylbenzyltriphenylphosphonium bromide, 4-chloromethylbenzyltriphenylphosphonium chloride, 2-chloromethylbenzyltriphenylphosphonium chloride, 3-chloromethylbenzyltriphenylphosphonium chloride, 4-iodomethylbenzyltriphenylphosphonium iodide, 2-iodomethylbenzyltriphenylphosphonium iodide and 3-iodomethylbenzyltriphenylphosphonium iodide; preferably 3-bromopropyltriphenylphosphonium bromide and / or 4-bromomethylbenzyltriphenylphosphonium bromide.
5. The preparation method according to any one of claims 1 to 4, wherein: The concentration of the catalyst in the aqueous solution is 0.01wt%-5wt%, preferably 0.1wt%-1wt%; Preferably, the concentration of the halogenated quaternary ammonium salt and / or the halogenated quaternary phosphonium salt in the aqueous solution is 1 wt%-20 wt%, preferably 5 wt%-10 wt%.
6. Acid- and alkali-resistant positively charged nanofiltration membrane prepared by the preparation method described in any one of claims 1 to 5.
7. The acid- and alkali-resistant positively charged nanofiltration membrane according to claim 6, wherein: The acid-base resistant positively charged nanofiltration membrane comprises a bottom layer, a porous support layer and an acid-base resistant separation layer in sequence; Wherein, the acid-base resistant separation layer is grafted with a quaternary ammonium salt group represented by formula I and / or a quaternary phosphonium salt group represented by formula II via N atoms; Wherein, R1 is a substituted or unsubstituted alkylene group of C1-C9; R2, R3, and R4 are each independently selected from a C1-C3 alkyl group or a phenyl group; R5 is a C1-C6 alkylene group, a phenyl group, or a C7-C10 aralkyl group; R6, R7, and R8 are each independently selected from a phenyl group or a C7-C10 aralkyl group; X is halogen.
8. The acid- and alkali-resistant positively charged nanofiltration membrane according to claim 7, wherein: R1 is a C1-C6 substituted or unsubstituted alkylene group, R2, R3, and R4 are each independently CH3; R5 is a C1-C3 alkylene group, a phenyl group, or a C8-C10 aralkyl group; R6, R7, and R8 are each independently phenyl group; Preferably, R1 is a C1-C3 substituted alkylene group, wherein the substituent is a hydroxyl group or a carboxyl group; Preferably, X is Cl, Br or I.
9. The acid-base resistant positively charged nanofiltration membrane according to any one of claims 6 to 8, wherein: The content of nitrogen atoms in the quaternary ammonium salt group in the acid-base resistant positively charged nanofiltration membrane is 0.5-6at.%, preferably 2-5at.%; Preferably, the content of phosphorus atoms in the acid-base resistant positively charged nanofiltration membrane is 0.4-3 at.%, preferably 0.5-2 at.%.
10. The acid-base resistant positively charged nanofiltration membrane according to any one of claims 6 to 9, wherein: The surface Zeta potential of the acid-base resistant positively charged nanofiltration membrane is 0-30 mV, preferably 5-20 mV.
11. The acid-base resistant positively charged nanofiltration membrane according to any one of claims 6 to 10, wherein: The average pore size of the acid-base resistant positively charged nanofiltration membrane is 0.1-0.5 nm, preferably 0.15-0.3 nm.
12. The acid-base resistant positively charged nanofiltration membrane according to any one of claims 6 to 11, wherein: The contact angle of the acid-base resistant positively charged nanofiltration membrane is 30-80°, preferably 30-60°.
13. The acid-base resistant positively charged nanofiltration membrane according to any one of claims 6 to 12, wherein: The thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the acid-base resistant separation layer is 10-500 nm, preferably 50-300 nm.
14. Application of the acid-base resistant positively charged nanofiltration membrane described in any one of claims 6 to 13 in the field of water treatment.
Citation Information
Patent Citations
Phosphonic chloride monomer, nanofiltration composite membrane and preparation method of nanofiltration composite membrane
CN107176963A
Anti-biological contamination reverse osmosis membrane, and preparation method and application thereof
CN110354682A
Acid / alkali-resistant composite nanofiltration membrane as well as preparation method and application thereof
CN113509839A
Polyamide composite membrane and preparation method thereof
CN115155338A
Surface quaternization modified nanofiltration membrane and preparation and application thereof in salt lake magnesium-lithium separation
CN115414791A